Language Functions in German Supermarket TV Commercials - Ellia Wamese; Jolanda Tomasouw; Kalvin Karuna (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
Commercials are unavoidable these days. They accompany us in everyday life. They are intended to motivate people to do something specific in the interests of the advertiser (Janich, 2013). There are plenty of studies conducted to examine the language function in advertisements. However, only few studies have been undertaken to investigate language function in commercials. Supriyono (2015) has conducted a study on language functions found in Mizone Fres’in TV Commercial based on Hymes and Grumperz’s (1964) theory of language function. Lestari (2018) has also investigated language functions, based on Jakobson (1960), used in twenty Maybelline commercials published in 2016 and 2018. Particular commercials were further studied in the present research, German supermarket TV Commercials, and which language function was emphasized. The results showed that the referential function was emphasized in the commercials.